Development of a high‐speed MALDI‐triple quadrupole mass spectrometric method for the determination of 3, 4‐methylenedioxymethamphetamine (MDMA) in oral fluid. Issue 2 (19th May 2015) - Poetzsch, Michael; Steuer, Andrea E.; Hysek, Cedric M.; Liechti, Matthias E.; Kraemer, Thomas
Abstract : 3, 4‐Methylenedioxymethamphetamine (MDMA, ecstasy) is still a widely used illicit designer drug and its detection in different matrices is of major importance for forensic purposes (e.g. driving under the influence) as well as for workplace drug testing or abstinence control. Established analytical methods for the determination of MDMA are mainly employing high performance liquid chromatography (HPLC) or gas chromatography (GC) coupled to mass spectrometric detection. Matrix assisted laser desorption/ionization‐triple quadrupole‐tandem mass spectrometry (MALDI‐QqQ‐MS/MS) is so far rarely used in forensics and offers an ultrafast high‐throughput platform. The Quantisal™ Oral Fluid Collection Device was used for sample collection. After addition of the deuterated internal standard and a carbonate buffer (0.75 M Na2 CO3 ), oral fluid samples were liquid‐liquid extracted (ButOAc/EtOAc, 1:1). As little as 1 microlitre of a mixture of this extract and the MALDI matrix (alpha‐cyano‐4‐hydroxycinnamic acid) was spotted onto the MALDI plate and could directly be analyzed. With MALDI omitting chromatographic separation, very short analysis times of about 10 s per sample were possible. The method was developed and validated according to international guidelines including specificity, recovery, matrix effects, accuracy and precision, stabilities and limit of quantification. All validation criteria were fulfilled except for ion suppression/enhancement. Comparison with a routine liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) method showed good agreement of the results. Applicability of the method was shown by analyzing about 250 oral fluid samples collected after controlled administration of 125 mg MDMA in a pharmacokinetic study. The whole lot of samples could be analyzed in less than 1 h, proving the ultra‐high‐speed of the method. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Quantification of MDMA in oral fluid samples using MALDI‐QqQ mass spectrometry with analysis times as short as 10 seconds per sample. All validation criteria were fulfilled for ion‐suppression/enhancement and the method was successfully applied to a clinical study.